Growth features of the Amur sleeper, Perccottus glenii (Actinopterygii: Perciformes: Odontobutidae), in the invaded Carpathian Basin, Hungary - K. Nyeste; S. Kati; S.A. Nagy; L. Antal (Acta Ichthyologica et Piscatoria, 2017)
Background. The Amur sleeper, Perccottus glenii Dybowski, 1877, is the most invasive alien fish species in the native aquatic communities in central Europe. Although the accelerated invasion of P. glenii has been well documented, there is little information on the ecological and growth parameters of non-native populations in this region. The aim of this study was to describe the growth features of the population of P. glenii in a shallow oxbow lake in the Carpathian Basin. Materials and methods. Our study sample consisted of 1239 individuals (628 ♂ + 611 ♀) collected from an oxbow lake near the Tisza River in the same month for three years (2013–2015). The length, weight, age structure, sex-dependent growth rate, and the condition factor of the collected specimens were determined. Results. The sex ratio was 0.49 (♀ ÷ (♀ + ♂)). The standard length and weight of the collected P. glenii specimens ranged from 20.7 to 127.7 mm and from 0.3 to 75.8 g, respectively. The length–weight relations (SL–W) were allometrically negative for the males (W = 3.2 × 10–5SL2.960), females (W = 3.8 × 10–5SL2.921), and both sexes (W = 3.5 × 10–5SL2.940), without significant differences between males and females. According to the length-frequency analysis, five age groups were differentiated. The von Bertalanffy growth models were L∞ = 138.87 mm, k = 0.21, t0 = –0.54 (♂), L∞ = 174.21 mm, k = 0.17, t0 = –0.33 (♀), L∞ = 154.01 mm, k = 0.19, t0 = –0.45 (♂ + ♀). The growth performance parameters were Ф′ = 3.61 (♂), Ф′ = 3.71 (♀), Ф′ = 3.65 (♂ + ♀), respectively. Conclusion. Due to unequal investment in reproduction, there was a significant difference in the growth rate between males and females. The literature data showed that invasive gobies and odontobutids (e.g., P. glenii) exhibit more opportunistic reproduction strategy in newly colonized areas, which may contribute to the invasion success. This strategy (e.g., earlier maturation, longer spawning period, etc.) results in slower growth rate due to energetic trade-off between reproduction and somatic growth. The observed growth rate of invasive Amur sleeper population (especially in the older age groups) was slower than that of native and more established naturalized populations in Eurasia.